Competition with Primary Sensory Afferents Drives Remodeling of Corticospinal Axons in Mature Spinal Motor Circuits - Jiang, Yu-Qiu (J Neurosci, 2016)
Injury to the mature motor system drives significant spontaneous axonal sprouting instead of axon regeneration. Knowing the circuit-level determinants of axonal sprouting is important for repairing motor circuits after injury to achieve functional rehabilitation. Competitive interactions are known to shape corticospinal tract axon outgrowth and withdrawal during development. Whether and how competition contributes to reorganization of mature spinal motor circuits is unclear. To study this question, we examined plastic changes in corticospinal axons in response to two complementary proprioceptive afferent manipulations: (1) enhancing proprioceptive afferents activity by electrical stimulation; or (2) diminishing their input by dorsal rootlet rhizotomy. Experiments were conducted in adult rats. Electrical stimulation produced proprioceptive afferent sprouting that was accompanied by significant corticospinal axon withdrawal and a decrease in corticospinal connections on cholinergic interneurons in the medial intermediate zone and C boutons on motoneurons. In contrast, dorsal rootlet rhizotomy led to a significant increase in corticospinal connections, including those on cholinergic interneurons; C bouton density increased correspondingly. Motor cortex-evoked muscle potentials showed parallel changes to those of corticospinal axons, suggesting that reciprocal corticospinal axon changes are functional. Using the two complementary models, we showed that competitive interactions between proprioceptive and corticospinal axons are an important determinant in the organization of mature corticospinal axons and spinal motor circuits. The activity- and synaptic space-dependent properties of the competition enables prediction of the remodeling of spared corticospinal connection and spinal motor circuits after injury and informs the target-specific control of corticospinal connections to promote functional recovery. SIGNIFICANCE STATEMENT Neuroplasticity is limited in maturity, but it is promoted after injury. Axons of the major descending motor pathway for motor skills, the corticospinal tract (CST), sprout after brain or spinal cord injury. This contributes to spontaneous spinal motor circuit repair and partial motor recovery. Knowing the determinants that enhance this plasticity is critical for functional rehabilitation. Here we examine the remodeling of CST axons directed by sensory fibers. We found that the CST projection is regulated dynamically in maturity by the competitive, activity-dependent actions of sensory fibers. Knowledge of the properties of this competition enables prediction of the remodeling of CST connections and spinal circuits after injury and informs ways to engineer target-specific control of CST connections to promote recovery.